2019
DOI: 10.5114/ada.2019.84595
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis in Poland is on the rise and underreported

Abstract: Introduction Despite the availability of diagnostic tests and effective treatment, there has been a problem with vigilance and reporting of that infectious disease in many countries including Poland. Aim To compare the incidence of syphilis in Poland in years 2010–2016 according to the mandatory epidemiological surveillance system with the data of the National Health Fund (NHF). Material and methods Data of the NHF in Poland were collected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In 2017, 1710 persons were infected with syphilis in Poland (Biuletyn Statystyczny Ministerstwa Zdrowia 2018). According to Teter et al (2019), these results are severely underestimated. His study shows that in the years 2010-2016, the number of syphilis cases in Poland according to NFZ (National Healthcare Fund) data was twice higher than what is indicated by the statistics of the obligatory system of epidemiological surveillance.…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, 1710 persons were infected with syphilis in Poland (Biuletyn Statystyczny Ministerstwa Zdrowia 2018). According to Teter et al (2019), these results are severely underestimated. His study shows that in the years 2010-2016, the number of syphilis cases in Poland according to NFZ (National Healthcare Fund) data was twice higher than what is indicated by the statistics of the obligatory system of epidemiological surveillance.…”
Section: Resultsmentioning
confidence: 99%
“…A study carried out in Poland reports that despite the availability of diagnostic tests and effective treatment, problems with surveillance and reporting of this infectious disease occur. Although notification to the epidemiological surveillance system is mandatory, health professionals' low awareness generates underreporting (Teter et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Syphilis is a sexually transmitted infection caused by Treponema pallidum (Chiquet et al, 2014). Epidemiological data indicate an increasing annual prevalence of syphilis, with the highest incidence among sexually transmitted diseases (STDs) (da Motta et al, 2018; Futami et al, 2019; Teter et al, 2019). Previous research has shown that T. pallidum possesses the ability to evade the host immune defenses, resulting in prolonged and persistent infections with serious clinical consequences (Li et al, 2013; Qin et al, 2015; Spagnuolo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%